ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V MI MAHAD AL-ZAYTUN - Siti Hajar; Dadan Mardani; iis humaeroh (STKIP Subang, 2025)
Learning is the foundation of education, where everything that is programmed will be implemented during the learning process. In this process, all subjects play an important role, including teachers, school principals and students themselves. Even though everything has been programmed, learning failures are still found due to obstacles or learning problems faced by students, one of which is in learning Indonesian. The researcher discovered a problem that caused the average grade V MI Ma'had Al-Zaytun students' scores on the results of the observation questionnaire to be below the predetermined KKM, namely 70. Therefore the aim of this research is to analyze and understand the difficulties studying class V MI Ma'had Al-Zaytun students in Indonesian language learning. The research method used in this research is descriptive qualitative, with data collection techniques including observation, interviews and documentation. The population in this study were all class V students at MI Ma'had Al-Zaytun and Indonesian language teachers, while the sample in this study was class V B05 students and class V Indonesian teachers. The results of the research show that students' learning difficulties in learning Indonesian in class V MI Ma'had Al-Zaytun are very diverse, including difficulties in understanding the material, difficulties in applying vocabulary and theory into practice, and students' learning motivation. Keywords: learning difficulties, Indonesian, madrasah ibtidaiyah